Similarity solution of the shock wave propagation in water - Muller M. (Applied and Computational Mechanics, 2007)
This paper presents the possibility of calculation of propagation of a shock wave generated during the bubble collapse in water including the dissipation effect. The used semi-empirical model is based on an assumption of similarity between the shock pressure time profiles in different shock wave positions. This assumption leads to a system of two ordinary differential equations for pressure jump and energy at the shock front. The NIST data are used for the compilation of the equation of state, which is applied to the calculation of the shock wave energy dissipation. The initial conditions for the system of equations are obtained from the modified method of characteristics in the combination with the differential equations of cavitation bubble dynamics, which considers viscous compressible liquid with the influence of surface tension. The initial energy of the shock wave is estimated from the energy between the energies of the bubble growth to the first and second maximum bubble radii.